Reliability of digital panoramic radiographs in detecting calcified carotid artery atheromatous plaques: A clinical study - Neha Khambete; Rahul Kumar; Mukund Risbud; Anil Joshi (Wolters Kluwer Medknow Publications, 2014)
Objectives: The objective of this study was to determine whether digital panoramic radiography is a reliable method to detect calcified carotid artery atheromatous plaques (CCAAP) as compared with ultrasonography. Study Design: Digital panoramic radiographs were obtained from 50 patients who also underwent carotid ultrasound examination. The images were interpreted by trained maxillofacial radiologist for the presence or absence of calcified atheromatous plaques. The extent of carotid calcification on carotid ultrasonography was determined by a trained Sonologist, which was considered as the gold standard assessment. Results: Digital panoramic radiographs had a sensitivity of 76% and specificity of 98.66% in determining CCAAP. There was a high level of agreement between diagnoses, with a kappa value of 0.8. Conclusion: To conclude, digital panoramic radiographs had good sensitivity and high specificity in detecting CCAAP. If properly trained, dentists can detect such plaques and can refer patients to physician for timely medical treatment.